Light induction of somatic embryogenesis in Arabidopsis is regulated by PHYTOCHROME E - Chan, A.; Stasolla, C.
The requirement of light on somatic embryogenesis (SE)has been documented in many species; however, no mechanism of action has been elucidated. Using Arabidopsis SE as a model, the effect of red light (660 nm)during the induction phase corresponding to the formation of the embryogenic tissue was examined. Analyses of several phytochrome mutants revealed that red light signaling, conducive to SE, was mediated by PHYTOCHROME E (PHYE). Both phyE and darkness were sufficient to repress the formation of somatic embryos and reduced the expression of CONSTITUTIVE PHOTOMORPHIC DWARF 3 (CPD3), a rate limiting step in brassinosteroid (BR)biosynthesis, as well as AGAMOUS LIKE 15 (AGL15), a key inducer of many SE genes. We further integrated BR signaling and nitric oxide (NO)with PHYE by demonstrating that applications of both compounds to phyE explants and WT explants cultured in the dark partially restored AGL15 expression. These results demonstrate that SE induction by red light operates via PHYE through BR signaling and NO required to induce AGL15.
Keywords: ARABIDOPSIS; BRASSINOSTEROIDS; LIGHT; PHYTOCHROME; SOMATIC EMBRYOGENESIS